Sprayed concrete and preparation method thereof
By adding polyvinyl butyral and glycolic acid to the sprayed concrete to form a copolymer, the problems of high rebound rate and insufficient bonding performance of sprayed concrete are solved, and the mechanical properties and construction quality of concrete are significantly improved.
Patent Information
- Application Number
- CN202411478909.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-28
AI Technical Summary
The rebound rate of existing sprayed concrete is high, resulting in poor construction quality and economic losses, and insufficient bonding performance, which can easily lead to the peeling of concrete slurry.
Polyvinyl butyral (PVB) and glycolic acid are added to the sprayed concrete. The two form copolymers through copolymerization reactions to improve the adhesion and mechanical properties of the concrete.
It significantly enhances the adhesion and overall mechanical properties of concrete, improves mechanical strength and durability, reduces rebound rate, and improves construction quality.
Smart Images

Figure CN119528494A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of shotcrete, and in particular to shotcrete and a preparation method thereof. Background Art
[0002] In tunnel construction, it is a common method to use shotcrete to reinforce the surrounding rock, so that it can form a complete, stable and strong structure to ensure construction safety. In addition to tunnel engineering, shotcrete is also used in many fields such as water conservancy and hydropower, slope protection, mining, underground engineering and engineering repair.
[0003] At present, during the construction of a highway section in Guizhou, construction workers found that the rebound rate of shotcrete was too high during on-site construction and the lack of construction technology caused great economic losses. The reason is that the construction environment of the Guizhou section is relatively harsh, with high humidity, strong wind speed, and large temperature differences at different altitudes, all of which will affect the spraying effect; on the other hand, the bonding performance of the current shotcrete slurry does not meet the construction requirements of this section, resulting in the concrete slurry being sprayed and attached to the rock, which is prone to peeling off.
[0004] At present, the consumption of shotcrete has increased dramatically with the increase in engineering projects. Ordinary shotcrete is generally composed of cement, fly ash, sand and gravel aggregate, water reducer and accelerator. Its rebound rate is mostly above 30%, and the dust rate is high, which causes a lot of waste. At the same time, it also affects the construction quality of shotcrete and causes certain safety hazards to the sprayers.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] In view of this, the present invention proposes a shotcrete and a preparation method thereof, which are used to solve the problem of high rebound rate of the current shotcrete.
[0007] The technical solution of the present invention is achieved as follows: The present invention provides a shotcrete, which comprises the following components by weight:
[0008] 20-35 parts of gel material,
[0009] 20-30 parts of fine aggregate,
[0010] 15-25 parts of coarse aggregate,
[0011] 1-3 parts of polyvinyl butyral,
[0012] Hydroxyacetic acid 0.5-2 parts,
[0013] 13-16 parts water.
[0014] Polyvinyl butyral (PVB) is a product of the reaction of polyvinyl alcohol (PVA) and butyraldehyde. It has good adhesion, flexibility and chemical resistance. Hydroxyacetic acid is an organic acid with a hydroxyl group and a carboxyl group. It can participate in a variety of chemical reactions and enhance the functionality of polymers.
[0015] The present invention adds polyvinyl butyral (PVB) and glycolic acid to concrete, and the copolymer formed by the mixture of the two improves the overall performance of concrete by improving the adhesion of concrete. Specifically, the molecular structure of polyvinyl butyral includes an acetal group formed by a vinyl main chain and butyraldehyde, and the main chemical formula is [-CH2-CH(O-Bu)-], wherein Bu represents the acetal group of butyraldehyde. The molecular formula of glycolic acid is HOCH2COOH. When polyvinyl butyral and glycolic acid undergo copolymerization, the carboxyl group (-COOH) in glycolic acid will undergo an esterification reaction with the hydroxyl group (-OH) remaining in PVB to form an ester bond (-COO-); at the same time, the acetal group (-O-Bu) in PVB will react with the hydroxyl group in glycolic acid to form a new chemical bond, resulting in the modification of the acetal group of PVB, thereby changing the physical and chemical properties of PVB, making it more suitable for combining with other components in concrete. Under certain conditions, a cross-linking reaction may occur between PVB and glycolic acid to form a three-dimensional spider web structure. This cross-linking reaction is through the hydroxyl and carboxyl groups in the glycolic acid molecules reacting with the functional groups in multiple PVB molecules to form a cross-linking structure. Through the above chemical reaction, the PVB-glycolic acid copolymer formed has significantly enhanced adhesion due to the formation of new chemical bonds; the copolymer has better dispersibility in concrete, which improves the overall mechanical properties of concrete; the cross-linking structure formed by the copolymer reaction improves the mechanical strength and durability of the copolymer.
[0016] On the basis of the above technical solution, preferably, the gel material comprises the following components by weight:
[0017] 15-25 parts of cement,
[0018] 5-10 parts of mineral admixture.
[0019] More preferably, the mineral admixture comprises the following components by weight:
[0020] 3-5 parts of fly ash,
[0021] 2-5 parts of silicon powder.
[0022] On the basis of the above technical solution, preferably, the following components are also included by weight: 1-7 parts of admixture.
[0023] More preferably, the admixture comprises the following components by weight:
[0024] Accelerator 0-1 part,
[0025] Water reducing agent 0-6 parts.
[0026] More preferably, the accelerator is an aluminum sulfate liquid alkali-free accelerator or sodium metasilicate pentahydrate, and the water reducer is a lignin sulfonate or naphthalene sulfonate water reducer or a polycarboxylic acid water reducer. The main function of the accelerator is to shorten the setting time. The water reducer is an admixture that can reduce the amount of mixing water while maintaining the fluidity of the cement paste. The water reducer can not only improve the working performance of the concrete, but also improve its strength and durability.
[0027] On the basis of the above technical solution, preferably, the fine aggregate is machine-made sand, and the apparent density of machine-made sand in dry state is 2.71 g / cm 3 The water absorption rate is 0.81%, the stone powder content is 14.0%, the fineness modulus is 2.76, the particle grading belongs to Zone Ⅱ, the grading is good, the methylene blue value is 0.6, the mud content meets the requirements of the specification, and its quality meets the quality requirements of aggregate for shotcrete.
[0028] On the basis of the above technical solution, preferably, the coarse aggregate is crushed stone, the crushed stone particle size range is 5mm-10mm, and the apparent density in dry state is 2.72g / cm 3 , the water absorption rate is 0.37%, and its quality meets the quality requirements of aggregate for shotcrete.
[0029] On the other hand, the present invention also provides a method for preparing shotcrete, which is used to prepare the above-mentioned shotcrete, comprising the following steps:
[0030] Step 1: According to the composition ratio of shotcrete, gel material, fine aggregate, coarse aggregate and water are weighed and added into a mixer and stirred evenly. The speed of the mixer is controlled to be 200 r / min, the stirring time is 5 min, and the stirring temperature is 20-30° C.;
[0031] Step 2: weigh polyvinyl butyral and glycolic acid according to the component ratio of shotcrete into the mixture obtained in step 1 and stir and mix them evenly, control the speed of the mixing mixer to 300 r / min, the stirring time to 5 min, and the stirring temperature to 20-30° C.;
[0032] Step 3, weigh the accelerator and water reducer into the mixture obtained in step 2 according to the component ratio of shotcrete and stir to mix, control the speed of the mixing mixer to 400r / min, the stirring time to 5min, the stirring temperature to 20-30°C, and obtain the shotcrete after stirring.
[0033] The sprayed concrete and preparation method thereof of the present invention have the following beneficial effects compared with the prior art:
[0034] The present invention adds polyvinyl butyral and glycolic acid as modified components to concrete, and the copolymer formed by the copolymerization reaction between the two significantly enhances the adhesion of the concrete; the dispersibility of the copolymer in the concrete is better, and the overall mechanical properties of the concrete are improved; the cross-linked structure formed by the copolymer reaction improves the mechanical strength and durability of the copolymer. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 is the SEM image of the baseline shotcrete;
[0037] Figure 2 is the SEM image of the shotcrete of Comparative Example 1;
[0038] Figure 3 is the SEM image of the shotcrete of Comparative Example 2;
[0039] Figure 4 is the SEM image of the shotcrete of comparative example 3;
[0040] Figure 5 This is the SEM image of the shotcrete with the composition ratio of the present invention. DETAILED DESCRIPTION
[0041] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] Example 1
[0043] The sprayed concrete of the present invention comprises the following components: 250g of cement, 30g of fly ash, 30g of silica fume, 250g of fine aggregate, 200g of coarse aggregate, 10g of polyvinyl butyral, 10g of glycolic acid, 10g of accelerator, 50g of water reducer and 150g of water. The components of cement include, by mass percentage, 58.01% of CaO, 19.72% of SiO2, 5.76% of Al2O3, 4.01% of Fe2O3, 2.03% of MgO, 2.77% of SO3, 0.42% of Na2O, 1.26% of K2O, and the balance is water, and the density is 3.06g / cm 3 The fly ash meets the national standard of Grade II. The fine aggregate is machine-made sand, and the apparent density of machine-made sand in dry state is 2.71g / cm 3 The water absorption rate is 0.81%, the stone powder content is 14.0%, the fineness modulus is 2.76, and the particle size distribution belongs to zone II; the coarse aggregate is crushed stone, the crushed stone particle size range is 5mm-10mm, and the apparent density in dry state is 2.72g / cm 3 The water absorption rate is 0.37%. The quick-setting agent is an aluminum sulfate liquid alkali-free quick-setting agent; the water-reducing agent is lignin sulfonate
[0044] The method for preparing shotcrete of this embodiment comprises the following steps:
[0045] Step 1: According to the composition ratio of shotcrete, gel material, fine aggregate, coarse aggregate and water are weighed and added into a mixer and stirred evenly. The speed of the mixer is controlled to be 200 r / min, the stirring time is 5 min, and the stirring temperature is 30° C.;
[0046] Step 2: weigh polyvinyl butyral and glycolic acid according to the component ratio of shotcrete into the mixture obtained in step 1 and stir to mix, control the speed of the mixing mixer to 300 r / min, the stirring time to 5 min, and the stirring temperature to 30° C.;
[0047] Step 3, weigh the accelerator and water reducer into the mixture obtained in step 2 according to the component ratio of shotcrete and stir to mix, control the speed of the mixing mixer to 400r / min, the stirring time to 5min, the stirring temperature to 30°C, and obtain the shotcrete after stirring.
[0048] Example 2
[0049] The difference between the shotcrete of the present invention and Example 1 is that 20 g of polyvinyl butyral and 10 g of glycolic acid are used, and the amounts of other components are the same as those in Example 1, and the preparation method is also the same.
[0050] Example 3
[0051] The difference between the shotcrete of the present invention and Example 1 is that 30 g of polyvinyl butyral and 10 g of glycolic acid are used, and the amounts of other components are the same as those in Example 1, and the preparation method is also the same.
[0052] Example 4
[0053] The difference between the shotcrete of the present invention and Example 1 is that 40 g of polyvinyl butyral and 10 g of glycolic acid are used, and the amounts of other components used are the same as those in Example 1, and the preparation method is also the same.
[0054] Example 5
[0055] The difference between the shotcrete of the present invention and Example 1 is that 20 g of polyvinyl butyral and 5 g of glycolic acid are used, and the amounts of other components used are the same as those in Example 1, and the preparation method is also the same.
[0056] Example 6
[0057] The difference between the shotcrete of the present invention and Example 1 is that 20 g of polyvinyl butyral and 20 g of glycolic acid are used, and the amounts of other components are the same as those in Example 1, and the preparation method is also the same.
[0058] Example 7
[0059] The difference between the shotcrete of the present invention and Example 1 is that 20 g of polyvinyl butyral and 25 g of glycolic acid are used, and the amounts of other components used are the same as those in Example 1, and the preparation method is also the same.
[0060] Example 8
[0061] The difference between the shotcrete of the present invention and Example 1 is that no accelerating agent and water reducing agent are added, 150g of water is used, and the amounts of other components used are the same as those in Example 1, and the preparation method is also the same. The difference between this embodiment and Example 1 is that the setting time of the concrete is longer, and the amount of water required to be added is greatly increased.
[0062] Comparative Example 1
[0063] The difference between this comparative example and Example 2 is that only 20 g of polyvinyl butyral component is added to the concrete. The preparation method is the same.
[0064] Comparative Example 2
[0065] The difference between this comparative example and Example 2 is that only 10 g of glycolic acid component is added to the concrete. The preparation method is the same.
[0066] Comparative Example 3
[0067] The shotcrete of this comparative example includes 250g of cement, 30g of fly ash, 30g of silica fume, 250g of fine aggregate, 200g of coarse aggregate, 30g of polyvinyl alcohol fiber, 10g of accelerator, 50g of water reducer, and 150g of water. The polyvinyl alcohol (PVA) fiber has a diameter of 16μm, a tensile strength of 1.81GPa, an elastic modulus of 40GPa, a fiber length of 12mm, and a density of 1.29g / cm 3 The polyvinyl alcohol fiber used in this comparative example also has the ability to improve the bonding performance of concrete and is used as a modified component of the currently commercially available high-bonding performance concrete. The preparation method is the same.
[0068] Blank example
[0069] The blank example is used as a reference shotcrete, which includes 250g of cement, 30g of fly ash, 30g of silica fume, 250g of fine aggregate, 200g of coarse aggregate, 10g of accelerator, 50g of water reducer, and 150g of water. The difference between the blank example and Example 2 is that polyvinyl butyral and glycolic acid components are not added to the concrete. The preparation method is the same.
[0070] The test samples of concrete of Examples 1 to 7, Comparative Examples 1 to 3 and the blank example were prepared, and tested by slump expansion test, the 28d mechanical properties and impermeability of each sample were tested, and the pore structure parameters of each sample were tested by mercury intrusion porosimetry (MIP). The test results are shown in Tables 1 and 2 below.
[0071] Table 1 Mechanical properties and anti-permeability properties of shotcrete of various embodiments at 28 days
[0072]
[0073] From the data comparison of Examples 1 to 4, it can be found that as the content of polyvinyl butyral increases gradually, the mechanical properties of the sample gradually increase, and gradually decrease after reaching the peak value (Example 2). From the data comparison of Examples 2 and 5 to 7, it can be found that as the content of glycolic acid increases gradually, the mechanical properties of the sample gradually increase, and gradually decrease after reaching the peak value (Example 2). From the data comparison of Example 2 and Comparative Example 1, and the data comparison of Comparative Example 1 and Examples 1, 3 and 4, it can be found that only polyvinyl butyral is added to the concrete without glycolic acid, and the mechanical properties of its sample are obviously inferior to the concrete sample to which polyvinyl butyral and glycolic acid are added at the same time, and the reason is that copolymer is not formed in the concrete. Similarly, from the data comparison of Example 2 and Comparative Example 2, and the data comparison of Comparative Example 2 and Examples 5 to 7, it can be found that only glycolic acid is added to the concrete without polyvinyl butyral, and the mechanical properties of its sample are also obviously inferior to the concrete sample to which polyvinyl butyral and glycolic acid are added at the same time. At the same time, from the data comparison of Example 2 and Comparative Example 3, it can be found that the mechanical properties of the sample of the present invention are also better than the concrete modified by PVA.
[0074] Table 2 Pore structure parameters of shotcrete 28d in various embodiments
[0075]
[0076] From the data comparison of Examples 1 to 4, it can be found that as the content of polyvinyl butyral increases gradually, the density of the microstructure of the sample increases gradually, reaches a peak value (Example 2) and then gradually decreases. From the data comparison of Examples 2 and 5 to 7, it can be found that as the content of glycolic acid increases gradually, the density of the microstructure of the sample increases gradually, reaches a peak value (Example 2) and then gradually decreases. From the data comparison of Example 2 and Comparative Example 1, and the data comparison of Comparative Example 1 and Examples 1, 3 and 4, it can be found that only polyvinyl butyral is added to the concrete without glycolic acid, and the density of the microstructure of its sample is obviously inferior to the concrete sample to which polyvinyl butyral and glycolic acid are added at the same time, and the reason is that copolymer is not formed in the concrete. Similarly, from the data comparison of Example 2 and Comparative Example 2, and the data comparison of Comparative Example 2 and Examples 5 to 7, it can be found that only glycolic acid is added to the concrete without polyvinyl butyral, and the density of the microstructure of its sample is also obviously inferior to the concrete sample to which polyvinyl butyral and glycolic acid are added at the same time. At the same time, from the comparison of the data of Example 2 and Comparative Example 3, it can be found that the density of the microstructure of the sample of the present invention is also better than that of the concrete modified by PVA.
[0077] At the same time, the microscopic morphology of the blank example, comparative examples 1 to 3 and embodiment 2 was detected by scanning electron microscopy (SEM). The SEM images of each sample were obtained as follows: Figures 1 to 5.
[0078] At present, researchers have classified the pores in concrete into harmless pores (pore size less than 20nm), less harmful pores (pore size 20nm-100nm), harmful pores (pore size 100nm-200nm) and more harmful pores (pore size greater than 200nm) according to the different effects of pore size on concrete strength. Therefore, if the pores below 50nm can be increased and the pores above 100nm can be reduced, it will help to significantly improve the performance of concrete. Figures 1 to 5 By comparison, it can be found that compared with other samples, the microstructure of the sample of the present invention is relatively dense, and the CSH gel and CH crystal hydration products are interlaced and filled with each other to form a relatively dense structure, which is also the reason why the mechanical properties of the sprayed concrete of the present invention are relatively high; in the sample of the present invention, fly ash has a good micro-aggregate filling effect, and its spherical particles can better fill the pores, resulting in a tighter structure, which is the main reason for the smaller porosity; the microstructure interface in the sample of the present invention is fuzzy, and the pores are densely filled with hydration products, which shows that the concrete is more viscous and the structure is more stable. The polymer is dispersed at the aggregate interface to form a polymer film layer, which can fill and block the interconnecting pores inside the concrete, and at the same time play the effect of refining the pores. It is estimated that this is the main reason why the most probable pore size, average pore size, and median pore size of the sample of the present invention are not significantly reduced, and the number of harmless pores and less harmful pores has a small increase. Therefore, after polyvinyl butyral and glycolic acid are added to the concrete of the present invention, the mechanical properties of the concrete are greatly improved, and its bonding performance is more excellent.
[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A shotcrete, characterized in that: By weight, it includes the following components: 20-35 parts of gel material, 20-30 parts of fine aggregate, 15-25 parts of coarse aggregate, 1-3 parts of polyvinyl butyral, Hydroxyacetic acid 0.5-2 parts, 13-16 parts water.
2. A shotcrete according to claim 1, characterized in that: The gel material comprises the following components by weight: 15-25 parts of cement, 5-10 parts of mineral admixture.
3. A shotcrete according to claim 2, characterized in that: The mineral admixture comprises the following components by weight: 3-5 parts of fly ash, 2-5 parts of silicon powder.
4. The shotcrete according to claim 1, characterized in that: The following components are also included by weight: 1-7 parts of additives.
5. The shotcrete according to claim 4, characterized in that: The admixture comprises the following components by weight: Accelerator 0-1 part, Water reducing agent 0-6 parts.
6. The shotcrete according to claim 5, characterized in that: The accelerator is an aluminum sulfate-based liquid alkali-free accelerator or sodium metasilicate pentahydrate, and the water reducer is a lignin sulfonate or naphthalene sulfonate water reducer or a polycarboxylic acid water reducer.
7. The shotcrete according to claim 1, characterized in that: The fine aggregate is machine-made sand, and the apparent density of the machine-made sand in dry state is 2.71 g / cm 3 The water absorption rate is 0.81%, the stone powder content is 14.0%, the fineness modulus is 2.76, and the particle size distribution belongs to Zone II.
8. The shotcrete according to claim 1, characterized in that: The coarse aggregate is crushed stone with a particle size range of 5mm-10mm and a dry apparent density of 2.72g / cm 3 , water absorption rate is 0.37%.
9. A method for preparing shotcrete, characterized in that: The method for preparing the sprayed concrete according to any one of claims 1 to 8 comprises the following steps: Step 1, according to the composition ratio of the shotcrete, the gel material, fine aggregate, coarse aggregate and water are weighed and added into a mixing mixer and stirred evenly, the speed of the mixing mixer is controlled to be 200r / min, the stirring time is 5min, and the stirring temperature is 20-30°C; Step 2, weighing polyvinyl butyral and glycolic acid according to the component ratio of shotcrete into the mixture obtained in step 1 and stirring and mixing, controlling the speed of the mixing mixer to 300 r / min, the stirring time to 5 min, and the stirring temperature to 20-30° C.; Step 3, weighing the accelerating setting agent and the water reducing agent into the mixture obtained in step 2 according to the component proportion of the shotcrete and stirring and mixing, controlling the speed of the mixing mixer to 400r / min, the stirring time to 5min, the stirring temperature to 20-30°C, and obtaining the shotcrete after stirring.